(untitled) (Journal of Forensic Medicine & Toxicology, 2021)
Ancient degraded remains of human origin can be identified using ancient DNA analyses. The mitochondrial DNA is a useful tool to solve unsolved cases in relation to identification of an individual where nuclear DNA is too degraded or insufficient to be used for the purpose. Comparative analysis of mtDNA content in petrous bone and the tooth-root cementum have revealed that later is best substrate for studying genomic analyses of ancient human populations The dental DNA is less prone to contamination, and the preservation of ancient DNA from dental samples is easier than bones. The selection of correct decontamination method, appropriate extraction protocol provides best results and thus increases value of bones and teeth as a forensic evidence in cases where identity establishment is problematic. In this review article, the current status of the methods used in ancient DNA research, the advantages and the limitations of this archaeogenetical method have been presented.